Evaluating nutrition and health impacts of agricultural innovations - Matin Qaim (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2014)
Agricultural innovations are seen as a key avenue to improve nutrition and health in smallholder farm households. But details of these agriculture-nutrition-health linkages are not yet well understood. While there is a broad literature on the adoption of agricultural technologies, most studies primarily focus on impacts in terms of productivity and income. Nutrition and health impacts have rarely been analyzed. In this article, we argue that future impact studies should include nutrition and health dimensions more explicitly. A conceptual framework is developed to clarify possible impact pathways. Different nutrition and health metrics are reviewed in terms of their strengths and weaknesses and criteria of choice for different study purposes. To evaluate impacts of particular innovations, the chosen metrics have to be compared between adopters and non-adopters, using a suitable sampling design. Approaches of how to deal with possible selection bias are discussed. Finally, selected empirical examples in which these metrics and methods were used in practice are reviewed.
Keywords: I15; I32; O12; O33; Q12; 330; food security; health; nutrition; agriculture; impact assessment; smallholder farmers